2023
DOI: 10.1186/s12931-023-02409-2
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict who will benefit most from biologics in severe asthma? A post-hoc analysis of two phase 3 trials

Abstract: Background Individualized prediction of treatment response may improve the value proposition of advanced treatment options in severe asthma. This study aimed to investigate the combined capacity of patient characteristics in predicting treatment response to mepolizumab in patients with severe asthma. Methods Patient-level data were pooled from two multinational phase 3 trials of mepolizumab in severe eosinophilic asthma. We fitted penalized regress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The DREAM RCT showed that the effects of mepolizumab were enhanced in patients with elevated blood eosinophils, and in those with higher airway reversibility (Ortega H. et al, 2014), and post hoc analyses of data from the DREAM and MENSA RCTs showed that the exacerbation rate reduction with mepolizumab increased progressively from 52% in patients with blood eosinophil count ≥150 cells/µL to 70% in patients with blood eosinophil count ≥500 cells/µL (Ortega et al, 2016). Other key predictors for treatment benefit for severe exacerbations included exacerbation history, baseline ACQ5 score and age, and those for symptom control included blood eosinophil count and presence of chronic rhinosinusitis with nasal polyps, which also benefitted from the treatment (Chen et al, 2023;Chupp et al, 2023;Liu et al, 2023). In the MAPLE trial on 27 patients treated with mepolizumab, addition of oral corticosteroids had no significant effect on symptoms or quality of life, but they did still improve smallairway obstruction and reduce T2 biomarkers (Yang et al, 2022).…”
Section: Anti-il-5 Treatment: Mepolizumab Reslizumab and Benralizumabmentioning
confidence: 99%
“…The DREAM RCT showed that the effects of mepolizumab were enhanced in patients with elevated blood eosinophils, and in those with higher airway reversibility (Ortega H. et al, 2014), and post hoc analyses of data from the DREAM and MENSA RCTs showed that the exacerbation rate reduction with mepolizumab increased progressively from 52% in patients with blood eosinophil count ≥150 cells/µL to 70% in patients with blood eosinophil count ≥500 cells/µL (Ortega et al, 2016). Other key predictors for treatment benefit for severe exacerbations included exacerbation history, baseline ACQ5 score and age, and those for symptom control included blood eosinophil count and presence of chronic rhinosinusitis with nasal polyps, which also benefitted from the treatment (Chen et al, 2023;Chupp et al, 2023;Liu et al, 2023). In the MAPLE trial on 27 patients treated with mepolizumab, addition of oral corticosteroids had no significant effect on symptoms or quality of life, but they did still improve smallairway obstruction and reduce T2 biomarkers (Yang et al, 2022).…”
Section: Anti-il-5 Treatment: Mepolizumab Reslizumab and Benralizumabmentioning
confidence: 99%
“…92 More broadly, multiple patient characteristics can be used to not only identify patients likely to have an enhanced response, but also those who likely to obtain minimal benefit from biologic treatments. 93 Such characterization is important, to improve the cost-effectiveness of these expensive therapies, and address the current practice of use beyond their evidence base for efficacy and safety. 94 An important example relevant to COPD is the utility of measurement of the blood eosinophil count to help identify in the clinic those patients with COPD who are likely to benefit most from ICS use at the lowest risk of undesired side effects.…”
Section: Traits To Guide Asthma/copd Treatmentmentioning
confidence: 99%